Metal tolerance in emerging clinically relevant multidrug-resistant Salmonella enterica serotype 4,[5],12:i:- clones circulating in Europe - Mourão, J (2015)
The occurrence of acquired metal tolerance genes in emerging MDR Salmonella enterica serotype 4,[5],12:i:- clones was assessed and their associated platforms and tolerance phenotype were characterised. Salmonella 4,[5],12:i:- from different sources belonging to European, Spanish and Southern European clones were studied. Screening for copper (pcoA-pcoD/tcrB), silver/copper (silA-silE), mercury (merA), arsenic (arsB) and tellurite (terF) tolerance genes was performed by PCR/sequencing. CuSO4/AgNO3 MICs were determined in aerobic/anaerobic atmospheres by agar dilution. Conjugation assays, genomic location and plasmid analysis were performed by standard procedures. Most isolates from European (98%) and Spanish (74%) clones carried silA-silE, contrasting with the Southern European clone (26%). merA/62% (European and Spanish clones) and pcoA-pcoD/50% (European clone) were also detected. merA ± pco + sil were chromosomally located in the European clone, whereas in Spanish and Southern European clones sil ± merA were within plasmids, both with antibiotic resistance genes. The pcoA-pcoD/silA-silE+ isolates showed higher MICCuSO4 in anaerobiosis than those without these genes (MIC50 = 24-28 vs. 2 mM). Different MICAgNO3 of silA-silE+ (MIC50 = 0.25 mM) and silA-silE-(MIC50 = 0.16 mM) isolates were observed in both atmospheres, with an MIC increment after prior exposure to silver (>3 vs. 0.08-0.125 mM) in aerobiosis. A high frequency of copper and silver tolerance, particularly among the two major Salmonella 4,[5],12:i:- MDR clones (European/Spanish) circulating in Europe and causing human infections, might facilitate adaptation/expansion of these strains in metal-contaminated environments, particularly copper in anaerobiosis. Furthermore, metal toxic concentrations in food-animal environments can contribute to persistence of genetic platforms carrying metal/antibiotic resistance genes in this foodborne zoonotic pathogen.